Application of Marker Assisted Backcrossing to Pyramid Salinity Tolerance (Saltol) into Rice Cultivar- Bac Thom 7 - Linh, Le Hung; Khanh, Tran Dang; Luan, Nguyen Van; Cuc, Dong Thi Kim; Duc, Le Duy; Linh, Ta Hong; Abdelbagi, M Ismail; Ham, Le Huy (VNU Journal of Science: Natural Sciences and Technology; Vol 28 No 2, 2012)
Abstract. Vietnam is one of the most vulnerable countries to climate change in Asia. Rice is a principle food in Vietnam and plays an important role in economy of the country. However, rice yield and its cultivating areas are adversely affected from the threats of devastation caused by the rise of sea level. Using marker assisted backcrossing (MABC) to develop a new salt tolerance rice variety is one of the feasible methods to cope with these devastating changes. To improve rice salt tolerance in Bac Thom 7 cultivar, FL478 was used as a donor parent to introgress the saltol QTL conferring salt tolerance into Bac Thom 7. Three backcrosses were conducted to transfer positive alleles of saltol from FL478 into Bac Thom 7. The plants number IL-30 and IL-32 in BC 3 F 1 population expected recurrent genome recovery of up to 99.2%, 100%, respectively. These selected lines that carried the saltol alleles were screened in field for their agronomic traits. All improved lines had saltol allele similar to the donor parent FL478, whereas their agronomic performances were the same as the original Bac Thom 7. We show here the success of improving rice salt tolerance by MABC and the high efﬁciency of selection in early generations. In the present study, MABC accelerated the development of superior qualities in the genetic background of Bac Thom 7. Keywords: Background selection, marker assisted backcross, rice, QTL.